Ranpirnase as a potential antitumor ribonuclease treatment for mesothelioma and other malignancies. (June 2008) - Beck, Amanda K; Pass, Harvey I; Carbone, Michele; Yang, Haining
Ranpirnase, originally isolated from oocytes of the northern leopard frog ( Rana pipiens ), is a member of the pancreatic RNase A superfamily of ribonucleases. Ranpirnase exerts antiproliferative and cytotoxic effects in  vitro and in  vivo and has been shown to act synergistically with different cancer therapeutic agents. The cytotoxic and cytostatic effects of ranpirnase are the consequence of tRNA degradation that results in the disruption of protein translation and the induction of programmed cell death (apoptosis). Ranpirnase has been shown to target malignant cells both in human cancer cell lines and in animal models, and has demonstrated efficacy in the treatment of several human cancers in clinical studies. Most clinical studies have been conducted in patients with malignant mesothelioma, and a confirmatory Phase  IIIb trial is currently underway for the treatment of this disease. Owing to its selective destruction of malignant cells and favorable toxicology profile, ranpirnase is a promising antitumor agent with ideal attributes that are generally lacking in conventional cytotoxic drugs.